Upright treadmill vs. semi-supine bicycle exercise echocardiography to provoke obstruction in symptomatic hypertrophic cardiomyopathy: a pilot study. (17th February 2017) - Reant, Patricia; Dufour, Maxence; Peyrou, Jerome; Reynaud, Amelie; Rooryck, Caroline; Dijos, Marina; Vincent, Cecile; Cornolle, Claire; Roudaut, Raymond; Lafitte, Stephane
Abstract: Aims: Recent findings regarding hypertrophic cardiomyopathy (HCM) haemodynamics emphasized the relationship between symptoms, left ventricular outflow tract obstruction (LVOTO), and the preload condition as the venous return level. As various types of exercises have different effects on peripheral vascular beds, this study sought to compare upright treadmill exercise echocardiography (EE) to semi-supine bicycle EE in maximum provoked LVOTO in HCM patients. Methods and results: Semi-supine bicycle and upright treadmill EE were prospectively performed in HCM patients with New York Heart Association functional Class II. Maximal LVOT gradient at rest in the supine and standing position, and during Valsalva manoeuvre, LVOT gradients of both semi-supine bicycle and treadmill exercise at peak and post-exercise, maximal exercise levels, and blood pressure adaptation were recorded. One patient was excluded for not sufficient image quality during treadmill. We studied 22/23 patients (mean age: 54.9 ± 12.3 yrs; 55% male). The supine position at rest displayed a mean maximal LVOT gradient of 46.1 ± 44.8 mmHg, which increased to 51.6 ± 41.2 mmHg during Valsalva ( P  = 0.066), and to 55.1 ± 37.8 mmHg in the standing position ( P  = 0.053). Mean maximal peak exercise LVOT gradient with semi-supine bicycle was significantly lower than in treadmill EE (54.6 ± 38.2 mmHg vs. 87.5 ± 42.1 mmHg, respectively, P  < 0.01). Among these patients, 41% exhibited LVOT gradient ≥ 30 mmHg at rest. Moreover, 41% exhibited LVOT gradient ≥ 50 mmHg during Valsalva, 55% in resting standing position, 41% at peak semi-supine bicycle exercise, 91% at peak treadmill exercise, and 95% in standing position during treadmill recovery period. Conclusion: This pilot study may suggest treadmill's greater value compared to semi-supine bicycle EE for determining maximum LVOT gradient in HCM.